An Analysis of Responses on the Earning Capacity Assessment Form-2. Issue 1 (10th June 2014) - Athanasou, James A.
<x content-type="archive" xml:space="preserve">Abstract</x> The Earning Capacity Assessment Form-2 assesses the factors that inhibit and facilitate an individual's return to work following an acquired disability (e.g., accident, misadventure). The purpose of this article is to provide the first item response analysis of the form. Data on Australian and US accident victims (N = 110) from two vocational assessment practices were used as a basis for evaluation. An item-response analysis was conducted using the Quest package for the 14 category responses. Results indicated that (a) the items function as inhibitors rather than drivers; and (b) they form a coherent underlying dimension of impairment. Problems in cognition and vocational adjustment issues were major markers for work incapacity.